Students readiness, motivation and attitude towards entrepreneurship - Samsudin Norsamsinar, Ab Jalil Norasibah, Ab Wahid Hariyaty, Yahaya Rusliza, Mat Jizat Jessnor Elmy (Universiti Pendidikan Sultan Idris, 2016)
Students readiness, motivation and attitude towards entrepreneurship by Samsudin Norsamsinar, Ab Jalil Norasibah, Ab Wahid Hariyaty, Yahaya Rusliza, Mat Jizat Jessnor Elmy,